The Analysis of the Composition of Greywater and the Effectiveness of a Household Greywater Treatment System - Huszár, Ágnes; Zseni, Anikó; Bakó-Dombi, Barbara (International Journal of Engineering and Management Sciences, 2018)
The purpose of the current study is to give comparable results to previous and further examinations concerning the quality of household generated greywater and to determine the effectiveness of a household wastewater treatment system treating only household generated greywater. Data for this study were collected from a household which avoids the production of black water at the source by using dry toilet. Water samples were collected from January 2017 until May 2017, altogether seven times. Samples were taken from 3 different places: (i) potable water from the kitchen tap, (ii) greywater sample from the first sewage tank of the household sewage treatment system and (iii) greywater sample from the fourth (last) sewage tank of the household sewage treatment system. A total of 16 physical, chemical and microbiological parameters were measured in the laboratory using the valid standard methods in each cases. The results of this investigation show that separating black water from greywater at the source by using dry toilet may produce considerably smaller environmental load. Lower emission values stems from the lower organic matter, nitrogen and phosphorus content of greywater.